2014
DOI: 10.1177/1087057113501553
|View full text |Cite
|
Sign up to set email alerts
|

A High-Content Screen Identifies Novel Compounds That Inhibit Stress-Induced TDP-43 Cellular Aggregation and Associated Cytotoxicity

Abstract: TDP-43 is an RNA binding protein found to accumulate in the cytoplasm of brain and spinal cord from patients affected with amyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration (FTLD). Nuclear TDP-43 protein regulates transcription through several mechanisms, and under stressed conditions it forms cytoplasmic aggregates that co-localize with stress granule (SG) proteins in cell culture. These granules are also found in the brain and spinal cord of patients affected with ALS and FTLD. The me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
62
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 29 publications
(60 reference statements)
4
62
1
Order By: Relevance
“…Recently, RNA granules have been implicated in many human diseases, including neurodegeneration, cancer, autoimmune diseases and infectious diseases [2, 4, 14, 15, 17, 58, 74, 76]. RNA granules (stress granules (SGs), processing bodies (p-bodies), nuclear paraspeckles, neuronal granules etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Recently, RNA granules have been implicated in many human diseases, including neurodegeneration, cancer, autoimmune diseases and infectious diseases [2, 4, 14, 15, 17, 58, 74, 76]. RNA granules (stress granules (SGs), processing bodies (p-bodies), nuclear paraspeckles, neuronal granules etc.)…”
Section: Discussionmentioning
confidence: 99%
“…A screen to identify compounds that decrease TDP-43 aggregation was performed in cell lines and many of the molecules identified were able to suppress the impaired motility phenotype of worms expressing mutant human TDP-43 (Boyd et al, 2013). …”
Section: Using C Elegans Model For Als Drug Discoverymentioning
confidence: 99%
“…Boyd and colleagues have shown that drugs identified from cell based systems often have relevance in C. elegans (Boyd et al, 2013). A screen to identify compounds that decrease TDP-43 aggregation was performed in cell lines and many of the molecules identified were able to suppress the impaired motility phenotype of worms expressing mutant human TDP-43 (Boyd et al, 2013).…”
Section: Using C Elegans Model For Als Drug Discoverymentioning
confidence: 99%
“…A screen to identify compounds that decrease TDP-43 aggregation was performed in cell lines and many of the molecules identified were able to suppress the impaired motility phenotype of worms expressing mutant human TDP-43 (Boyd et al, 2013).…”
Section: Using C Elegans Model For Als Drug Discoverymentioning
confidence: 99%